(3HgLI GdCSQGQ heYOf GdCfhGQ aj efGbH GdSGOI GdCNjGQ ef GdeTGjN GdCHQGQs - (3Ydj Hf jhSa Hf MQjR Hf eYVGO GddNej, CHh GdMSf, GdTWfhaj,J (B713 (3g` s ((3YHO GdQMef Hf eMeO Hf YHO GdQMef GdNdjdi s)
(3ChdgG (B:s
(3GSJaJM HGH GdYhf HGjOi eMGeQGf cdgG hGSJfLM SYi GdbUO HGjGQjg GdaQO s
(3BNQgG (B:s
(3deG hVYJ GHfi YHO GdbGOQ cGf dG jQVY KOjI ai fgGQ QeVGf bO bOe THGHi Yf gPG GdCeQ s
(3jdjgG NeS hQbGJ ef Chd cJGH (B" (3aJhM GdZjH (B" (3ddTjN YHO GdbGOQ GdLjdGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B264s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B326 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B51 s
Keywords: (3GdJGQjNs